Nerve Conduction Study (NCS) in Patients with Cervical Radiculopathy at Arifin Achmad General Hospital, Riau Province - Sukiandra, Riki; Putri, Azzahra Nur Aulya; Juananda, Desby; Maryanti, Yossi (Frontiers on Healthcare Research, 2025)
Background: Radiculopathy is one of the most common causes of neck pain in everyday clinical practice. Radiculopathy can occur in the cervical segment. The prevalence of cervical radiculopathy is lower than lumbar radiculopathy. NCS is an attempt to confirm the diagnosis of radiculopathy. This study aims to describe the NCS findings in cervical radiculopathy patients at RSUD Arifin Achmad, Riau Province. Methods: This descriptive quantitative study was conducted from January to September 2024 at RSUD Arifin Achmad, Riau Province, using total sampling. Data from NCS tests, including latency, amplitude, nerve conduction velocity (NCV), and F-wave parameters for motor and sensory nerves, were analyzed using descriptive statistics. Result: The majority of the results were ≥40 years old (69.2%), female (61.5%), and predominance of one extremity testing in cervical radiculopathy (60%). NCS of cervical radiculopathy motor, n.medianus latency was elongated (5.13 ± 2.22 ms), amplitude was normal (4.42 ± 3.03 mV), and KHS was decreased (46.50 ± 11.79 m/s). The n.ulnaris latency lengthened (4.49 ± 5.53 ms), amplitude shortened (5.02 ± 2.70 mV), and KHS decreased (46.44 ± 16.51 m/s). The n.radialis latency (2.34 ± 0.98 ms), amplitude (3.25 ± 0.98 mV), and KHS (78.91 ± 27.47 m/s) were normal. Cervical radiculopathy sensory NCS, n.medianus latency was normal (2.86 ± 0.51 ms), amplitude shortened (19.37 ± 19.38 µV), and KHS decreased (43.82 ± 20.27 m/s). In n.ulnaris, latency lengthened (3.30 ± 1.78 ms), amplitude was normal (17.13 ± 13.98 µV), and KHS decreased (42.62 ± 16.63 m/s). The n.medianus (26.47 ± 2.74 ms) and ulnar (24.83 ± 1.63 ms) F-waves were normal. Conclusion: NCS findings in cervical radiculopathy patients at RSUD Arifin Achmad reveal prolonged distal latency, decreased nerve conduction velocity, and reduced amplitude, suggesting demyelination and axonal loss. These results reinforce the role of NCS as a key diagnostic tool for cervical radiculopathy. Further research is needed to evaluate its correlation with clinical severity.